ANALISIS VERBAL DAN NONVERBAL PADA MANTRA PENGOBATAN SEBAGAI MEDIA PENYEMBUHAN DI MASYARAKAT KEDIRI: KAJIAN ETNOLINGUISTIK - Nur Lailiyah; Subardi Agan; Sardjono Sardjono (ppjbsip, 2022)
Abstract: The purpose of this study will be to reveal the verbal form, meaning and verbal function of the treatment spells used in the treatment of traditional healers. This research is a field research that uses a qualitative descriptive method with a literature study technique. Based on the results of the analysis, it can be seen that the form of healing spells consists of perfect and imperfect spells. The forms of healing spells consist of free rhymes, sects, quints, adultery and poetry. Has the function of curing stomach ailments, colds, internal heat, witchcraft, headaches. Healing diseases traditionally, verbal and nonverbal behavior is an inseparable unity. This is caused by several things including, (a) verbal behavior is an embodiment of faith and hope in God, (b) nonverbal behavior is a manifestation of real action, and (c) the existence of energy possessed by shamans or tetulung.